Oral multivalent epitope vaccine, based on UreB, HpaA, CAT, and LTB, for prevention and treatment of Helicobacter pylori infection in C57BL / 6 mice. Issue 3 (12th April 2021) - Xie, Wenwei; Zhao, Wenfeng; Zou, Ziling; Kong, Lingyi; Yang, Lei
Abstract: Background: As the resistance of Helicobacter pylori to traditional triple therapy is gradually revealed, an increasing number of people are focusing on vaccine treatments for H .  pylori infection. Epitope vaccines are a promising strategy for the treatment of H .  pylori infection, and multivalent vaccines will be more effective than monovalent vaccines. Materials and methods: In this study, we designed a multivalent vaccine named LHUC, which consists of the adjuvant LTB as well as three Th cell epitopes (HpaA154‐171, UreB237‐251, and UreB546‐561 ) and five B‐cell epitopes (UreB349‐363, UreB327‐334, CAT394‐405, CAT387‐397, and HpaA132‐141 ) from UreB, HpaA, and catalase. In BALB/c mice, the specificity and immunogenicity of the fusion peptide LHUC and the neutralization of H .  pylori urease and catalase by the specific IgG elicited by LHUC were evaluated. The preventive and therapeutic effects of LHUC were evaluated in C57BL/6 mice infected with H .  pylori . Results: The results showed that compared with LTB and PBS, LHUC induced specific IgG and IgA antibody production in mice, and IgG antibodies significantly inhibited the H .  pylori urease and catalase activities in vitro. Additionally, by detecting the levels of IFN‐γ, IL‐4, and IL‐17 in lymphocyte supernatants, we proved that LHUC could activate Th1, Th2, and Th17 mixed T‐cell immune responses in vivo. Finally, a C57BL/6 mouse model of gastric infection with H .  pylori was established. The results showed that compared with the effects of LTB and PBS, the prevention and treatment effects of oral inoculation with LHUC significantly inhibited bacterial colonization. Conclusions: In conclusion, LHUC, a multivalent vaccine based on multiple H .  pylori antigens, is a promising and safe vaccine that can effectively reduce the colonization of H .  pylori in the stomach.